2000
DOI: 10.1182/blood.v96.12.3948.h8003948_3948_3952
|View full text |Cite
|
Sign up to set email alerts
|

Level of minimal residual disease after consolidation therapy predicts outcome in acute myeloid leukemia

Abstract: We used flow cytometry to quantify minimal residual disease (MRD) in 56 patients with acute myeloid leukemia (AML) expressing a leukemia-associated phenotype. Thirty-four patients aged 18 to 60 years were entered into the AML-10 protocol (induction, consolidation, and autologous stem-cell transplantation [ASCT]), whereas 22 patients older than 60 years received the AML-13 protocol (induction, consolidation, and consolidation II). After induction, the level of MRD that was best associated with treatment outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
2
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 18 publications
6
101
2
2
Order By: Relevance
“…In particular, a very early time-point for WT1 monitoring (postinduction) [15,35,[36][37][38][39][41][42][43], but also a later time-point (postconsolidation or pre-allo-SCT) [38,[41][42][43] have been reported to significantly predict the outcome. Concerning LAIP-MFC sensitivity and efficiency, our data are concordant with those reported by the GIMEMA group and suggest that the most accurate predictive time-point of MRD assessment is probably after consolidation [14,44]. In particular, we have seen that, within favorable and intermediate-risk groups, MRD positivity after consolidation predicts relapse in about 40% of MRD-positive AML patients, but the accuracy of relapse prediction increases to 75% when the evaluation of MRD positivity is made after intensification.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, a very early time-point for WT1 monitoring (postinduction) [15,35,[36][37][38][39][41][42][43], but also a later time-point (postconsolidation or pre-allo-SCT) [38,[41][42][43] have been reported to significantly predict the outcome. Concerning LAIP-MFC sensitivity and efficiency, our data are concordant with those reported by the GIMEMA group and suggest that the most accurate predictive time-point of MRD assessment is probably after consolidation [14,44]. In particular, we have seen that, within favorable and intermediate-risk groups, MRD positivity after consolidation predicts relapse in about 40% of MRD-positive AML patients, but the accuracy of relapse prediction increases to 75% when the evaluation of MRD positivity is made after intensification.…”
Section: Discussionsupporting
confidence: 90%
“…In one study, 46 of 53 patients had phenotypes that were found at frequencies of less than one in 10 4 cells in normal bone marrow, while seven had phenotypes found in normal bone marrow but at frequencies of less than one in 10 3 (San Miguel et al, 1997). In another study, 65 of 93 patients had a phenotype suitable for detection of one leukaemic cell in 10 4 normal cells (Venditti et al, 2000).…”
Section: Immunophenotypes For Mrd Studies By Flow Cytometrymentioning
confidence: 98%
“…At present, it is well established that MRD assessment is an important factor in predicting risk of relapse and/or death (Venditti et al, 2000;San Miguel et al, 2001;Feller et al, 2004;Kern et al, 2004;D ıez-Campelo et al, 2009;Terwijn et al, 2013). MRD assessment will therefore be included in risk group stratification in upcoming clinical studies (e.g.…”
Section: Association Between Cd34 and Mrdmentioning
confidence: 99%